One‐Step Synthesis of Dicarboxamides through Pd‐Catalysed Aminocarbonylation with Diamines as N‐Nucleophiles. Issue 8 (3rd February 2015) - Carrilho, Rui M. B.; Almeida, Ana R.; Kiss, Mercédesz; Kollár, László; Skoda‐Földes, Rita; Dąbrowski, Janusz M.; Moreno, Maria José S. M.; Pereira, Mariette M.
Abstract: An efficient one‐step synthetic strategy was used to prepare a set of dicarboxamides through palladium‐catalysed aminocarbonylation of iodoalkenyl and iodoaryl compounds, with use of various alkyl‐ and aryldiamines as N‐nucleophiles. The isolated yields of the dicarboxamides depended significantly on the iodo substrate and diamine structures, as well as on the reaction conditions, the best one (ca. 70 %) being achieved with 1‐iodocyclohexene as substrate and 1, 4‐diaminobutane as nucleophile, at 100 °C and 30 bar of CO. When iodobenzene was used as model aryl halide, the highest yield of the target dibenzamides (ca. 65 %) was obtained with 1, 4‐diaminobenzene as coupling amine, at 100 °C and 10 bar of CO. Preliminary studies on their in vitro cytotoxicity against human lung carcinoma A549 cells showed N, N ′‐(butane‐1, 4‐diyl)dibenzamide and androst‐16‐ene‐based dicarboxamides to be the most efficient cytotoxic agents, with IC50 values of approximately 40 μM . Abstract : The one‐step synthesis of a set of dicarboxamides was accomplished through palladium‐catalysed aminocarbonylation of iodoalkenyl and iodoaryl compounds, with use of diamines as N‐nucleophiles. The cytotoxic activities of some of the diamides against human lung carcinoma A549 cancer cells have been preliminarily appraised.